Dynamic Response and Fatigue Analysis of a New Marine Gravitational Energy Storage System Under Wave Loads - Ziheng Wang; Dazhi Huang; Hongkun He; Feifei Yang; Wenhao Li; Yi Chen (Journal of Marine Science and Engineering)
Given the unstable input of electricity generated by offshore renewable energy in connection to the power grid at present, one solution is energy storage technology. In recent years, the new marine gravitational energy storage technology has received wide attention in China and worldwide. To apply this new energy storage technology for use in the ocean, in view of the structural characteristics of the new offshore gravitational energy storage system, a support structure based on the foundation of a wind-powered pipe frame is proposed. In order to verify the feasibility of the support structure, a finite element model is established using SACS to analyze whether it meets the requirements. The construction of this structure in a specific sea is simulated through finite element simulation. Then, in accordance with the hydrogeological conditions of the sea area, the wind turbine data, and the dimensional parameters of the energy storage system’s structure, a finite element model is established with SACS for static analysis, modal analysis, random wave response analysis, and wave spectrum fatigue analysis, thereby determining whether the structure meets the requirements for strength, deformation, and fatigue. The research results show that the UC value of the static strength of the support structure of the new offshore gravitational energy storage system is less than 1. In the modal analysis, the natural frequencies of the first- and second-order modes are not within the danger range. In the corresponding random wave analysis, it is found that the natural frequencies of the first four orders are the greatest contributors to the dynamic response during the normal operation of the turbine. In fatigue analysis, it is concluded that the structure meets all the requirements of DNV specifications. The research results provide a reference for the engineering application of the support structure of the new gravitational energy storage system in the ocean.